Kajian Tentang Kelompok Tani Bunga Krisan (Chrysanthemum Morifolium) di Kenagarian Aie Batumbuak Kecamatan Gunung Talang Kabupaten Solok - Yulia, Nora Sofika; Erita, Yeni; U, Iswandi (Pendidikan Geografi, 2013)
This study aimed to obtain the data, process, analyze and discuss: 1) work motivation in Sub-District Aie Batumbuak District Gunung Talang Solok Regency, 2) work experience in Sub-District Aie Batumbuak District Gunung Talang Solok Regency, 3) marketing in Sub-District Aie Batumbuak District Gunung Talang Solok Regency.This type of research is classified in one of the descriptive research study aimed to look at in accordance with the data that was collected through the images or descriptive variables. The study population was all chrysanthemum farmer group members. In Aie Batumbuak. Samples were taken in two ways, the first sample area, namely the purposive sampling technique, the ellipse that has 3 chrysanthemum farmer groups, namely Jorong Koto Baruah, Madang and Sangkak Puyuah. Samples were taken with a total sampling techniques, which all members of the chrysanthemum farmer groups, totaling 41 samples. Guided data collection using questionnaires, statistical analysis used was descriptive using percentage formula.The results include: 1) Motivation chrysanthemum farmer group members in Sub-District Aie Batumbuak generally quite high, but the weekdays are generally 2-3 days / week (43.90%), 2) Work experience chrysanthemum farmer group members in Sub-District Aie Batumbuak generally very controlled (73.71%) each existing agricultural extension, but it would be very capable if experts from outside the area to practice cultivation of chrysanthemums this, because they are still not enough if only the experience of agricultural extension alone because too other much needed knowledge and 3) marketing process plant chrysanthemums in Sub-District Aie Batumbuak is generally not standard or can be increased and also decreased each year (41.46%), because they are caused by buyer demand process yields no similar to what is expected.